Accuracy of Orthognathic Surgical Planning using Three-dimensional Virtual Techniques compared with Conventional Two-dimensional Techniques: a Systematic Review - Thomas Starch-Jensen; Federico Hernández-Alfaro; Özlem Kesmez; Romario Gorgis; Adaia Valls-Ontañón (Stilus Optimus, 2023)
Objectives: The objective was to assess the accuracy of orthognathic surgical planning using three-dimensional virtual planning compared with conventional two-dimensional planning. Material and Methods: MEDLINE (PubMed), Embase and Cochrane Library search combined with hand-search of relevant journals was conducted to identify randomized controlled trials (RCTs) published in English through August 2nd, 2022. Primary outcomes included postsurgical accuracy of hard and soft tissue. Secondary outcomes included treatment planning time, intraoperative time, intraoperative blood loss, complications, financial expenses, and patient-reported outcome measures (PROMs). Quality and risk-of-bias assessment were evaluated by Cochrane risk of bias tool and GRADE system. Results: Seven RCTs characterised by low, high, and unclear risk of bias fulfilled inclusion criteria. Included studies disclosed conflicting results regarding accuracy of hard and soft tissue as well as treatment planning time. The intraoperative time was shortened, and financial expenses were increased with three-dimensional virtual surgical planning (TVSP), while no planning-related complications were revealed. Comparable improvement in PROMs were reported with TVSP and two-dimensional planning. Conclusions: Future orthognathic surgical planning will indisputable be performed by three-dimensional virtual planning. The financial expenses, treatment planning time, and intraoperative time will therefore probably decrease due to further development of three-dimensional virtual planning techniques. The hard and soft tissue accuracy between planned position and achieved surgical outcome seems to be improved by three-dimensional virtual planning compared with two-dimensional planning, although results are inconsistent. Further development of three-dimensional virtual planning involving cutting guides and patient-specific osteosynthesis plates are therefore needed to improve the accuracy of orthognathic surgical planning.